Linking Individual Movements to a Skilled Repertoire: Fast Modulation of Motor Synergies by Repetition of Stereotyped Movements. (6th August 2019) - Fricke, Christopher; Gentner, Reinhard; Alizadeh, Jalal; Classen, Joseph
Abstract: Motor skills emerge when practicing individual movements enables the motor system to extract building instructions that facilitate the generation of future diverse movements. Here we asked how practicing stereotyped movements for minutes affects motor synergies that encode human motor skills acquired over years of training. Participants trained a kinematically highly constrained combined index-finger and thumb movement. Before and after training, finger movements were evoked at rest by transcranial magnetic stimulation (TMS). Post-training, the angle between posture vectors describing TMS-evoked movements and the training movements temporarily decreased, suggesting the presence of a short-term memory for the trained movement. Principal component analysis was used to identify joint covariance patterns in TMS-evoked movements. The quality of reconstruction of training or grasping movements from linear combinations of a small subset of these TMS-derived synergies was used as an index of neural efficiency of movement generation. The reconstruction quality increased for the trained movement but remained constant for grasping movements. These findings suggest that the motor system rapidly reorganizes to enhance the coding efficiency of a difficult movement without compromising the coding efficiency of overlearned movements. Practice of individual movements may drive an unsupervised bottom-up process that ultimately shapes synergistic neuronal organization by constant competition of action memories.